Sistem Informasi Suhu Tubuh Pada Gate Berbasis Nodemcu ESP32 - Yande Hendika Bayu Perdana; I Gusti Made Ngurah Desnanjaya; I Kadek Susila Satwika (Faculty of Computer Science, University of Jember, 2022)
Covid-19 is a deadly virus that spreads very quickly through droplets. A person infected with the Covid-19 virus usually experiences symptoms of a fever whose body temperature exceeds 37.5°C. One way to find out a person's body temperature can be done by screening. The filtering method usually uses a tool called a thermogun. To operate a special officer's thermogun, but there is a possibility for the officer to spread or be infected with the Covid-19 virus. To overcome this problem, in this study a tool in the form of an automatic doorstop that can check the temperature was made. This tool is also equipped with an information system. The information system in question is a website, this website is useful for recording everyone who enters. The input of this information system is temperature and image. The information system can be monitored directly by officers online. The appearance of this website is in the form of the date the visitor entered the place, the temperature of the visitor, and the visitor's image. Testing is done by sending the temperature value obtained by the temperature sensor to the database and displayed on the website. The temperature delivery success rate is 100% from 10 times of testing. While the ESP32 Camera used can send images to the database and display on the website with a success rate of 80% from 10 times of testing.